Recombinant factor VIIA is associated with an improved 24‐hour survival without an improvement in inpatient survival in massively transfused civilian trauma patients - Nascimento, Bartolomeu (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2011)
OBJECTIVE: To determine whether recombinant factor VIIa (rFVIIa) is associated with increased survival and/or thromboembolic complications. INTRODUCTION: Uncontrollable hemorrhage is the main cause of early mortality in trauma. rFVIIa has been suggested for the management of refractory hemorrhage. However, there is conflicting evidence about the survival benefit of rFVIIa in trauma. Furthermore, recent reports have raised concerns about increased thromboembolic events with rFVIIa use. METHODS: Consecutive massively transfused (≥ 8 units of red blood cells within 12 h) trauma patients were studied. Data on demographics, injury severity scores, baseline laboratory values and use of rFVIIa were collected. Rate of transfusion in the first 6 h was used as surrogate for bleeding. Study outcomes included 24‐hour and in‐hospital survival, and thromboembolic events. A multivariable logistic regression analysis was used to determine the impact of rFVIIa on 24‐hour and in‐hospital survival. RESULTS: Three‐hundred and twenty‐eight patients were massively transfused. Of these, 72 patients received rFVIIa. As expected, patients administered rFVIIa had a greater degree of shock than the non‐rFVIIa group. Using logistic regression to adjust for predictors of death in the regression analysis, rFVIIa was a significant predictor of 24‐hour survival (odds ratio (OR) =  2.65; confidence interval 1.26–5.59; p = 0.01) but not of in‐hospital survival (OR = 1.63; confidence interval 0.79–3.37; p = 0.19). No differences were seen in clinically relevant thromboembolic events. CONCLUSIONS: Despite being associated with improved 24‐hour survival, rFVIIa is not associated with a late survival to discharge in massively transfused civilian trauma patients.